Thermodynamic Model for Updraft Gasifier with External Recirculation of Pyrolysis Gas - Fajri Vidian; Adi Surjosatyo; Yulianto Sulistyo Nugroho (Journal of Combustion)
Most of the thermodynamic modeling of gasification for updraft gasifier uses one process of decomposition (decomposition of fuel). In the present study, a thermodynamic model which uses two processes of decomposition (decomposition of fuel and char) is used. The model is implemented in modification of updraft gasifier with external recirculation of pyrolysis gas to the combustion zone and the gas flowing out from the side stream (reduction zone) in the updraft gasifier. The goal of the model obtains the influences of amount of recirculation pyrolysis gas fraction to combustion zone on combustible gas and tar. The significant results of modification updraft are that the increases amount of recirculation of pyrolysis gas will increase the composition of H2 and reduce the composition of tar; then the composition of CO and CH4 is dependent on equivalence ratio. The results of the model for combustible gas composition are compared with previous study.